Pendidikan Akal dalam Perspektif Islam - Endang Sutisna; Mahmudi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
of the Koran about intellectual education, and the function of intellectual education in an Islamic perspective. Reasonable education, or what is also known as rational education, has an important role in shaping thinking, morality and behavior. individual in Islam. In this context, research will examine the Islamic view of reason as the main instrument in the process of human learning and development. The method used in this research is descriptive qualitative. This research produces conclusions in the form of data that describes in detail, not data in the form of numbers (Lexy J. Moleong, 2008). This research is a type of library research, namely research that The object of study uses library data in the form of books as a data source (Sutrisno Hadi, 2002). The research results show that from an Islamic perspective, reason is a special gift given by Allah SWT which will later help humans to carry out their role as caliphs on earth. Reason is given as a gift that must be developed and used wisely. Intellectual education aims to ensure that a person develops his intellect and controls his desires through education, so that a person will become a person who is mentally tough, confident, will not easily fall into vice and is ready to face the tests of life. Intellectual education functions to achieve the essential truth in gathering knowledge (collecting the knowledge), solving the problems faced (problem solving), and looking for more efficient ways to fulfill the goals to be achieved (finding a way).